Neovascularization induced by hypoxia inducible transcription factor is associated with the improvement of cardiac dysfunction in experimental autoimmune myocarditis. (February 2014) - Tada, Yuko; Ogawa, Masahito; Watanabe, Ryo; Zempo, Hirofumi; Takamura, Chisato; Suzuki, Jun-ichi; Dan, Takashi; Miyata, Toshio; Isobe, Mitsuaki; Komuro, Issei
<x xml:space="preserve">Abstract</x> Objective: Mechanisms of cardiac dysfunction in myocarditis have not been fully elucidated. Though it remains controversial whether angiogenesis is beneficial or harmful in inflammatory disease, significant vascular destruction might possibly impair cardiac function in myocarditis. The prolyl hydroxylase domain-containing protein (PHD) inhibitor is a potential drug for promoting angiogenesis as it stabilizes hypoxia inducible transcription factor (HIF). The authors examine whether the PHD inhibitor TM6008 could affect cardiac function by promoting angiogenesis in experimental autoimmune myocarditis (EAM). Methods: EAM was induced on BALB/c mice by immunizing them with a synthesized α myosin heavy-chain peptide. Every day, 200 mg/kg of TM6008 or vehicle was administered orally. Results: TM6008 improved left ventricular ejection fraction significantly on the 21st day of EAM. Though TM6008 did not affect the severity of myocardial cell infiltration, it tended to reduce cardiac fibrosis. Immunohistochemistry showed that CD31-positive blood vessels were preserved in the TM6008 group compared to the control group. Immunoblotting revealed that TM6008 increased the expression of HIF-1α, HIF-2α and vascular endothelial growth factor in myocarditis. Conclusion: Inhibition of PHD could ameliorate cardiac dysfunction in EAM, partially through promoting neovascularization. Relief of tissue hypoxia via neovascularization could improve cardiac function in myocarditis.